Pengaruh Psychological Safety terhadap Sustainable Innovation dengan Communication Behavior sebagai Variabel Mediasi - Mustahidda, Rahmania; Adelyana Sari, Zahra (CV. ALIM'SPUBLISHING, 2026)
Abstract. This study aims to analyze the influence of psychological safety on sustainable innovation with communication behavior as a mediating variable. The research design used a quantitative approach with a survey method on employees of PT Morich Indo Fashion. Sampling was conducted using the Slovin formula and obtained respondents who were analyzed using Partial Least Squares (PLS). The results showed that psychological safety has a positive effect on sustainable innovation and communication behavior. In addition, communication behavior also has a positive effect on sustainable innovation and mediates the relationship between psychological safety and sustainable innovation. These findings emphasize the importance of creating a psychologically safe climate and effective communication to encourage sustainable innovation in organizations. Keywords: Psychological Safety; Communication Behavior; Sustainable Innovation; Partial Least Squares; Human Resource Management